2021
DOI: 10.3390/diagnostics11020335
|View full text |Cite
|
Sign up to set email alerts
|

Optimized Identification of High-Grade Prostate Cancer by Combining Different PSA Molecular Forms and PSA Density in a Deep Learning Model

Abstract: After skin cancer, prostate cancer (PC) is the most common cancer among men. The gold standard for PC diagnosis is based on the PSA (prostate-specific antigen) test. Based on this preliminary screening, the physician decides whether to proceed with further tests, typically prostate biopsy, to confirm cancer and evaluate its aggressiveness. Nevertheless, the specificity of the PSA test is suboptimal and, as a result, about 75% of men who undergo a prostate biopsy do not have cancer even if they have elevated PS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 47 publications
1
10
0
Order By: Relevance
“…However, prostate cancer screening has been surrounded by controversy and can be seen as an ethical dilemma. Studies have shown that distinguishing between indolent pathology and aggressive tumors using PSA levels alone is insufficient as it is not cancer-specific (7). It is also a challenge as high PSA levels do not directly correlate with pathogenicity and requires further investigations through multiparametric magnetic resonance imaging (MRI) and histology.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, prostate cancer screening has been surrounded by controversy and can be seen as an ethical dilemma. Studies have shown that distinguishing between indolent pathology and aggressive tumors using PSA levels alone is insufficient as it is not cancer-specific (7). It is also a challenge as high PSA levels do not directly correlate with pathogenicity and requires further investigations through multiparametric magnetic resonance imaging (MRI) and histology.…”
Section: Introductionmentioning
confidence: 99%
“…It is also a challenge as high PSA levels do not directly correlate with pathogenicity and requires further investigations through multiparametric magnetic resonance imaging (MRI) and histology. Therefore, early diagnosis often leads to harm to patients via overdiagnosis and unnecessary treatment (radical surgery, radiotherapy and chemical castration) leading to reduced quality of life (QoL) and psychological trauma knowing they have a cancer diagnosis (7). This chapter aims to address the developmental processes involved in prostate cancer including hereditary and molecular components.…”
Section: Introductionmentioning
confidence: 99%
“…We recently demonstrated that by using artificial neuronal networks (ANNs), it is possible to develop models combining different PSA-derivatives (including total PSA, free PSA, p2PSA and PSA density) optimizing high-grade PCa recognition [ 39 ]. Taking into account that AI is revolutionizing PCa clinical management [ 40 , 41 ] and ameliorates accuracy in the detection of csPCa when applied to MRI [ 42 ], it is plausible to hypothesize that the sequential or the combined use of novel biomarkers and MRI based on machine learning approach may produce models able to minimize overdiagnosis, without missing csPCa, providing the clinicians a tool to match tumor aggressiveness and treatment invasiveness.…”
Section: Discussionmentioning
confidence: 99%
“…In this respect, our group struggled with the use of additional biomarkers for identification of clinically significant prostate cancer (PCa) and recognised a potential of PSA molecular forms that should not be dismissed [ 1 ]. We also noted that the model combining different biomarkers offers the potential for better diagnostic performance [ 2 , 3 ]. Thus, as clinical studies will confirm the relevance of other variables for PCa diagnosis, we will be able to include them in this model template, increasing even further sensitivity, specificity, and accuracy.…”
mentioning
confidence: 99%